Quantifying the economic cost of antibiotic resistance and the impact of related interventions: Rapid methodological review, conceptual framework and recommendations for future studies - Jit, M; Ng Hui Lin, D; Luangasanatip, N; Sandmann, F; Atkins, KE; Robotham, J; Pouwels, KB (BioMed Central, 2020)
Background: Antibiotic resistance (ABR) poses a major threat to health and economic wellbeing worldwide. Reducing ABR will require government interventions to incentivize antibiotic development, prudent antibiotic use, infection control, and deployment of partial substitutes such as rapid diagnostics and vaccines. The scale of such interventions needs to be calibrated to accurate and comprehensive estimates of the economic cost of ABR.